(untitled) (San Francisco, 2005)
Reinventing Public Health offers guidance for translating the growing body of research on the fundamental social, economic, and ecological determinants of health into innovative programs and policies to improve the health of populations.
Keywords: Public health,Social medicine,Health Policy,Y tế,Y học xã hội,Chính sách y tế; Social aspects,Khía cạnh xã hội